2017
DOI: 10.1111/liv.13503
|View full text |Cite
|
Sign up to set email alerts
|

DAMP molecular IL‐33 augments monocytic inflammatory storm in hepatitis B‐precipitated acute‐on‐chronic liver failure

Abstract: DAMP molecular IL-33 augmented the 'storm' of monocytic inflammation in response to LPS through ERK1/2 activation during HB-ACLF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…Although emerging evidence demonstrates that DAMPs released after the massive necrosis of hepatocytes contribute to the development of liver failure 11,32,33 , the potential role of extracellular gp96 in immune-mediated liver damage during liver failure has not been determined. Here, we first found that serum gp96 levels in patients with CHB and ACLF were elevated, which correlated with clinically relevant parameters in patients with ACLF, including ALT levels and the key pro-inflammatory cytokines TNF-α and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Although emerging evidence demonstrates that DAMPs released after the massive necrosis of hepatocytes contribute to the development of liver failure 11,32,33 , the potential role of extracellular gp96 in immune-mediated liver damage during liver failure has not been determined. Here, we first found that serum gp96 levels in patients with CHB and ACLF were elevated, which correlated with clinically relevant parameters in patients with ACLF, including ALT levels and the key pro-inflammatory cytokines TNF-α and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Seric IL-33 and ST2s concentrations are highly elevated compared to those in healthy donors and, interestingly enough, they are correlated with the severity of hepatic cytolysis (129, 130). In HBV acute-on-chronic liver failure (ACLF) (129), seric IL-33 and ST2s concentrations are pronouncedly higher than the concentrations observed in CHB patients. The circulating monocytes in ACLF patients present a highly activated and pro-inflammatory phenotype, which is correlated with IL-33 production.…”
Section: Contribution Of Il-1 Superfamily Of Cytokines To Hepatic Dismentioning
confidence: 96%
“…From this standpoint, IL-33 expression in LSEC significantly increases in patients with chronic HBV (CHB) infection, and is likewise highlighted in the hepatocytes of lesions/inflammatory foci in patients with the most severe form of hepatitis (129). Seric IL-33 and ST2s concentrations are highly elevated compared to those in healthy donors and, interestingly enough, they are correlated with the severity of hepatic cytolysis (129, 130). In HBV acute-on-chronic liver failure (ACLF) (129), seric IL-33 and ST2s concentrations are pronouncedly higher than the concentrations observed in CHB patients.…”
Section: Contribution Of Il-1 Superfamily Of Cytokines To Hepatic Dismentioning
confidence: 99%
“…Serum macrophage inflammatory protein 3 α levels also predict the severity of HB-ACLF [18]. Additionally, other inflammatory mediators, e.g., CXCL10 [19], extracellular histones [20], and DAMP molecular IL-33 [21], have been observed to closely relate with the prognosis of ACLF.…”
Section: Discussionmentioning
confidence: 99%